1996
DOI: 10.1148/radiology.201.3.8939239
|View full text |Cite
|
Sign up to set email alerts
|

Are MR imaging signs of meniscocapsular separation valid?

Abstract: The PPV for the MR diagnosis of meniscocapsular separation is low; the reported MR signs correlate poorly with arthroscopic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 0 publications
1
38
0
4
Order By: Relevance
“…Although this finding may not be used when the fat layer between meniscus and MCL is absent, the fat layer is present in most cases along the anterior portion of the MCL and, in about half the cases, along the mid portion of the MCL. Another potential problem is that the outer meniscal margin as vi sualized on MR images may not correspond to the true margin of the meniscus as seen histo logically becausethe peripheral 10â€"30% of the meniscus usually has vascular penetration, whereas the inner portion is avascular [3,7,9]. Therefore, the MR appearance of the inner and outer zones of the meniscus may be quite dif ferent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this finding may not be used when the fat layer between meniscus and MCL is absent, the fat layer is present in most cases along the anterior portion of the MCL and, in about half the cases, along the mid portion of the MCL. Another potential problem is that the outer meniscal margin as vi sualized on MR images may not correspond to the true margin of the meniscus as seen histo logically becausethe peripheral 10â€"30% of the meniscus usually has vascular penetration, whereas the inner portion is avascular [3,7,9]. Therefore, the MR appearance of the inner and outer zones of the meniscus may be quite dif ferent.…”
Section: Discussionmentioning
confidence: 99%
“…However, precise criteria for apply ing this sign have never been described. Rubin et al [3] reported that this sign is insensitive be cause displacements of up to 10 mm may be seen in the absence of meniscocapsular separa tion, whereas patients with meniscocapsular separation may not have any such displace ment. Our results support this finding because none of the cases with meniscocapsular separa tion showed any meniscal displacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16, 17). This could also be mistaken for evidence of an MCL sprain (10,11). Deeper involvement may include peripheral meniscal tears.…”
Section: Meniscocapsular Separationmentioning
confidence: 99%